IMPLEMENTASI DIRECT INSTRUCTION BERBASIS MODUL TUTOR SEBAYA PADA PENGOPERASIAN SOFTWARE PENGOLAH ANGKA(MS.EXCEL) SMK NEGERI I JENEPONTO - Halimatullah Halimatullah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
The study is a classroom action research which aims at enhancing learning activities of students and enhancing their learning result by implementing direct instruction with peer tutor module-based in operation spreadsheet software (Ms.Excel) at SMKN 1 Jeneponto. The subjects of the study were students og grade X TKJ at SMKN 1 Jeneponto of academic year 2013/2014 with as many as 45 students consistec of 19 male and 26 female students. The procedure of classroom action recearch used path model of action research based on hopkins which consisted of the planning phase, the implementation, supervision/evaluation, and reflection. All of the learning tools used in the study were validated by the experts and practitioners and had revision to obtain the feasible result to be used. The result of the study reveal that there is enhancement of activities and learning result of students of grade X TKJ at SMKN 1 Jeneponto in operating spreadsheet software (Ms.Excel) of basic competence, which explained the types and function of the spreadsheet software after the students were given direct instruction learning with peer tutor module-based